(untitled) - Suryanarayana, Narasipur Venkataram (Boston, 2003)
This text is intended for mechanical engineering majors taking a thermal design course. It combines practical coverage of thermal/fluid components and systems, with review coverage of prerequisite thermodynamics, fluid mechanics and heat transfer. Extensive case studies and practical examples show students how the thermal design is done, and the techniques used to simulate and optimize such designs
Keywords: Heat engineering,Engineering design